INTEGRATING AI INTO SYSTEMATIC LITERATURE REVIEW METHODOLOGY IN LITERARY STUDIES: A HYBRID FRAMEWORK - Abdullayeva Gavkharoy Sultonmakhmud kizi (Bright Mind Publishing, 2025)
This article proposes an innovative and practical hybrid model that integrates Artificial Intelligence (AI) tools into the systematic literature review (SLR) process, specifically within the field of literary studies. By blending the computational capabilities of AI with the nuanced interpretative expertise of human researchers, this hybrid approach aims to enhance research accuracy, efficiency, and replicability. The article explores recent developments in AI-assisted research methods and outlines a structured five-step model that promotes critical reading, transparency, and ethical AI use. The approach is intended to benefit both academic researchers and educators by supporting high-quality literary analysis through an augmented methodology.
Keywords: Artificial Intelligence, Systematic Literature Review, Literary Studies, PRISMA, Hybrid Framework, Interpretive Rigor.